Gall bladder perforation: critical analysis of management at tertiary care centre - Sharma, Sanjay; Trehan, Vikram; Ranjan, Priya; Singh, Amit (International Surgery Journal, 2023)
Background: Gall bladder perforation (GBP) is a rare complication of acute cholecystitis. Despite considerable advancements in diagnostic and therapeutic modalities, morbidity and mortality continues to be high, owing to delay in diagnosis and ill-defined treatment protocols. Methods: We reviewed demographic profile, diagnosis and management strategies employed in 28 patients at our centre from Jan 2018 till Jul 2020. Patients were classified based on Niemeier classification. Results: A total of 28 patients were identified but 3 excluded due to paucity of data. There were 21 patients of Niemeier type II perforation and 02 each of type I and III. Diagnosis of GBP was based on CECT in 18 patients. In patients with type II perforation, 03 underwent emergency laparoscopic cholecystectomy (LC) though one required conversion. Twelve patients were managed conservatively followed by interval cholecystectomy after mean duration of 14 weeks. Of these 08 successfully underwent LC and 03 were converted to open surgery. One patient underwent open radical cholecystectomy due to intraoperative suspicion of carcinoma. 06 patients of type II perforation underwent percutaneous drainage of collection followed by LC after mean duration of 23 weeks. Histopathology revealed chronic cholecystitis in 16 patients, acute cholecystitis in 05, carcinoma in 02 and xantho-granulomatous cholecystitis in one patient. Conclusions: CECT should be employed early for diagnosis in suspected cases and percutaneous intervention should be used in cases unresponsive to conservative measures alone. There are higher chances of success in performing LC after 14 weeks leading to better outcomes.